A importância do Anopheles darlingi Root, 1926 e Anopheles marajoara Galvão e Damasceno, 1942 na transmissão de malária no município de Macapá/AP - Brasil - GALARDO, Allan Kardec Ribeiro (Universidade Federal do Pará, 2014)
Malaria in the municipality of Macapá is mainly peri urban, which are characterized by flooding area, presence of forest fragments and disorganized settlements. The aim of this study was to determine the importance of Anopheles darlingi e Anopheles marajoara in the malaria transmission in Macapá. The study was carried out from October 2007 to September 2008, in the Lagoa dos Índios community, Macapá. It was collected 4,601 mosquitoes, from which 3,029 were Anopheles marajoara (65,8%), 917 Anopheles darlingi (19,9%), 429 Anopheles braziliensis (9,3%), 208 Anopheles triannulatus (4,5%), 18 Anopheles peryassui (0,4%) and 5 Anopheles nuneztovari (0,1%). Only 32.8% (1.511) of the adult mosquitoes were collected indoors and 67.2% (3.090) outdoors. The index of the bites by man and by hour for An. darlingi in the intradomicile had ranged from 0 to 6.5 and in the peridomicile from 0 a 22. As for the An. marajoara the range was from 0 to 22 in the intradomicile and from 0 to 175.5 in the peridomicile. The analysis of the exuvia and the genitalia dissecation had resulted in the confirmation of the two species, An. darlingi and An. marajoara, and that the An. marajoara is the only albitarsis complex specie that is circulating in the study area. The vectors abundance had flutuated associated with the sazonal pattern of the rain. An. darlingi is the most frequent at the beginning and end of the rain, while An. marajoara was present, in high density, during the rainy season. From the 4,601 tested mosquitoes, 100 were positive for human malaria parasites by the ELISA method with a infection index of 2.17%. The infection index for An. marajoara was 2,34% (71/3,029) and for An. darlingi 3.05% (28/917). This study had demonstrated that the two studied species are responsible for the malaria transmission maintenance during the whole year, thus confirming the importance of both.